Analisis Kesediaan dan Kemampuan Membayar terhadap Persepsi Kewajaran Tarif LRT Jabodebek pada Jam Sibuk dan Non-Sibuk (Studi Kasus: Stasiun Harjamukti) - Sehati Sumaryani; Pio Ranap Tua Naibaho (Jurnal Talenta Sipil, 2026)
High mobility in the Greater Jakarta (Jabodetabek) area, which is dominated by private vehicle use, has led to congestion and transportation inefficiency. The LRT Jabodebek was introduced as a mass transit alternative; however, its passenger occupancy rate remains suboptimal. This study aims to analyze the influence of Willingness to Pay (WTP) and Ability to Pay (ATP) on fare fairness perception during peak and off-peak hours, as well as to identify the dominant variable. A quantitative method with descriptive and verificative approaches was employed through a Likert-scale questionnaire distributed to users at Harjamukti Station. The data were analyzed using multiple linear regression. The results indicate that both WTP and ATP have a positive and significant effect on fare fairness perception. During peak hours, WTP is the dominant variable, whereas ATP is more dominant during off-peak hours. A fare of IDR 20,000 during peak hours tends to be rejected, while a fare of IDR 10,000 during off-peak hours is more acceptable. These findings suggest the need for a time-based fare policy to improve affordability and user acceptance.